Therapeutic effects of Fc gamma RIV inhibition are mediated by selectively blocking immune complex-induced neutrophil activation in epidermolysis bullosa acquisita - Haeger, Swantje C.; Kridin, Khalaf; Pieper, Mario; Griewahn, Laura; Nimmerjahn, Falk; Zillikens, Detlef; König, Peter; Ludwig, Ralf J.; Hundt, Jennifer E. (Frontiers in Immunology, 2022)
Epidermolysis bullosa acquisita (EBA) is a subepidermal autoimmune bullous disease caused by autoantibodies targeting type VII collagen (COL7). It is characterized by inflammation and subepidermal blistering mainly through immune complex (IC)-mediated activation of neutrophils. In experimental EBA, binding of neutrophils to ICs in the skin and induction of clinical disease depends on the expression of the Fc gamma receptor (FcγR) IV. As activating FcγR mediate both neutrophil extravasation and activation, we used multiphoton imaging to obtain further insights into the mechanistic contribution of FcγRIV in the pathogenesis of EBA. First, we demonstrated that blocking FcγRIV function completely protects LysM-eGFP mice against induction of antibody transfer-induced EBA. To visualize the interactions of anti-COL7 IgG and neutrophils in vivo, fluorescently labeled anti-COL7 IgG was injected into LysM-eGFP mice. Multiphoton microscopy was sequentially performed over a period of 8 days. At all time points, we observed a significantly higher extravasation of neutrophils into the skin of mice treated with anti-FcγRIV antibody compared to controls. However, the percentage of detected neutrophils localized to the target antigen along the dermal-epidermal junction was comparable between both groups. Additionally, reactive oxygen release and migration in vitro assay data demonstrate that FcγRIV antibody treatment inhibits the activation, but not the migration, of neutrophils. Our findings underscore the importance of advanced in vivo imaging techniques to understand the complexity of IC-mediated neutrophil-dependent inflammation, and indicate that the therapeutic utility of FcγRIV blockade is achieved through impairment of IC-mediated neutrophil activation.
CRIS-Team Scopus Importer:2022-11-04
Keywords: EBA; epidermolysis bullosa acquisita; Fc gamma receptor; immune complex; multiphoton imaging; neutrophil